1992
DOI: 10.1002/em.2850200208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of captan on dna and dna metabolic processes in human diploid fibroblasts

Abstract: The fungicide Captan has been examined for its effects on DNA and DNA processing in order to better understand the genotoxicity associated with this agent. Captan treatment resulted in production of DNA single strand breaks and DNA-protein cross-links and elicited an excision repair response in human diploid fibroblasts. Captan was also shown to inhibit cellular DNA synthesis and to form stable adducts in herring sperm and human cellular DNA. Misincorporation of nucleotides into Captan-treated synthetic DNA te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…DNA strand breaks and micronuclei are induced as a consequence of RS, which in turn leads to genomic instability. Our study demonstrates that captan exposure in mammalian cells induces various genotoxic effects, corroborating previous in vivo reports (Legator ; Feng and Lin ; Snyder ) and suggesting that these mechanisms could play a role in carcinogenesis. Moreover, our in vitro results on human peripheral lymphocytes, showing DNA damage with alkaline comet assay after captan treatment (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…DNA strand breaks and micronuclei are induced as a consequence of RS, which in turn leads to genomic instability. Our study demonstrates that captan exposure in mammalian cells induces various genotoxic effects, corroborating previous in vivo reports (Legator ; Feng and Lin ; Snyder ) and suggesting that these mechanisms could play a role in carcinogenesis. Moreover, our in vitro results on human peripheral lymphocytes, showing DNA damage with alkaline comet assay after captan treatment (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 92%
“…However, the mutagenic potency of captan has long been reported in Ames strains TA1535 and TA104 and also in the Escherichia coli WP2 uvrA strain (Bridges ; Barrueco and de la Pena ; Ohta et al ), revealing base‐change substitution on AT or GC base pairs, as well as in mammalian cellular mutation assays (O'Neill et al ; Edgar et al ). In addition to its mutagenic activity, the genotoxic potential of captan is supported by the induction of DNA breaks leading to chromosomal aberrations in mammalian cells (Swenberg et al ; Tezuka et al ; Snyder ). Finally, a direct interaction of captan with DNA and/or proteins linked to chromatin such as histones, polymerases or topoisomerase II, has been suggested (Anderson and Rosenkranz ; Couch and Siegel ; Couch et al ; Selsky and Matheson ; Dillwith and Lewis ; Pritchard and Lappin ; Snyder ; Grilli et al ; Provan et al ; Provan and Eyton‐Jones ; Rahden‐Staron ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 22 Captan is able to interact with DNA, especially to form DNA adducts and DNA-protein crosslinks 23 and more specifically inducing mutation through base-pair substitution mechanisms including those detected by TA102 or TA104 Salmonella typhimurium strains. 24 25 Recent studies have confirmed the ability of captan to be highly mutagenic on strains detecting base-pair mutations, 26 27 and not on strains sensitive to frameshift mutations such as *Including farmers without any protective devices (4 for mixing and 7 for application), with protective clothes alone (1 for mixing and 1 for application), with mask alone (3 for mixing and 1 for application).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism underlying the genotoxic effects is not well known, several reports have suggested that captan may interact with DNA (Anderson and Rosenkranz, 1974;SCC, 1981) and induce DNA repair (Swenberg et al, 1976;Ahmed et al, 1977;Simmon et al, 1977). Snyder (1992) indicated that captan induces a type of DNA damage recognized by the excision repair system in human fibroblasts and that captan-induced DNA damage may be at least partially repaired via a long-patch repair system. The DNA-damaging and repair-inducing character of captan has been verified using the nick translation assay (Nose and Okamoto, 1983;Snyder and Matheson, 1985).…”
Section: Primary Dna Damage As Comet Inductionmentioning
confidence: 99%